2013
DOI: 10.1007/s00454-013-9551-8
|View full text |Cite
|
Sign up to set email alerts
|

Extendability of Continuous Maps Is Undecidable

Abstract: We consider two basic problems of algebraic topology, the extension problem and the computation of higher homotopy groups, from the point of view of computability and computational complexity.The extension problem is the following: Given topological spaces X and Y , a subspace A ⊆ X, and a (continuous) map f : A → Y , decide whether f can be extended to a continuous mapf : X → Y . All spaces are given as finite simplicial complexes and the map f is simplicial.Recent positive algorithmic results, proved in a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 23 publications
0
42
0
Order By: Relevance
“…, k. Equivalently, Y is path-connected and the first k homotopy groups πi(Y ), i ≤ k, are trivial. 7 Steenrod [53] calls this restriction "most severe," and conjectures that it "should ultimately be unnecessary." encountered in applications, is the sphere S d .…”
Section: New Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, k. Equivalently, Y is path-connected and the first k homotopy groups πi(Y ), i ≤ k, are trivial. 7 Steenrod [53] calls this restriction "most severe," and conjectures that it "should ultimately be unnecessary." encountered in applications, is the sphere S d .…”
Section: New Resultsmentioning
confidence: 99%
“…The dimension and connectivity assumptions in Theorem 1.1 turned out to be essential and almost sharp, in the following sense: In [7], it is shown that, for every d ≥ 2, the extension problem is undecidable for dim X = 2d and Dependence on d. The running-time of the algorithm in Theorem 1.1 can be made polynomial for every fixed d, as was mentioned above, but it depends on d at least exponentially. We consider it unlikely that the problem can be solved by an algorithm whose running time also depends polynomially on d. One heuristic reason supporting this belief is that Theorem 1.1 includes the computation of the stable homotopy groups π d+k (S d ), k ≤ d − 2.…”
Section: Follow-up Workmentioning
confidence: 98%
See 1 more Smart Citation
“…We devise another way of converting Anick's Y into a simplicial complex, which produces only polynomially many simplices. 4 The idea is simple, but there are several technical issues to be worked out; we refer to [4] for the derivation of Theorem 1.2 from Anick's result.…”
Section: New Resultsmentioning
confidence: 99%
“…This survey summarizes the results of the three papers [12,5,4]. Together these comprise well over 100 pages, and they deal with numerous moderately advanced topological concepts, as well as many algorithmic notions and results.…”
Section: Introductionmentioning
confidence: 99%